Challenges of second language teachers' professional identity construction: Voices from Afghanistan. Issue 3 (4th March 2021) - Nazari, Mostafa; Miri, Mir Abdullah; Golzar, Jawad
Abstract : Afghanistan has recently witnessed the redefinition of its educational policies, particularly those related to language teaching. However, little is known about Afghan second language (L2) teachers and the challenges they might face in their professional identity construction. This study investigated the challenges of professional identity construction of Afghan L2 teachers. Scenario prompts and semistructured interviews were used to explore how the teachers responded to challenging situations and narrated their professional challenges. Data analyses indicated that the teachers responded to the scenario prompts in accordance with perspectives mirroring criticality in educational functioning by promoting learners' awareness of sociocultural anomalies, resisting institutional inequalities, and gearing instruction to learners' needs. Additionally, analysis of the teachers' semistructured interviews revealed sociocultural, institutional, and pedagogical challenges, particularly the dominance of institutional barriers in sanctioning the teachers' identity construction. The authors argue that Afghan L2 teachers need more assistance from policymakers and teacher educators to facilitate their professionalism and professional practice.